IMPLEMENTASI METODE ANALYTICAL HIERARCHY PROCESS (AHP) UNTUK PENILAIAN KINERJA KARYAWAN BERBASIS WEBSITE - Mochammad Hilmi Yahya; Mohammad Zoqi Sarwan (Jurnal Fakultas Teknologi Informasi, 2023)
Employees are one of the most important assets owned by the company in its efforts to maintain its survival, development, ability to compete, and profit. Competition in the business world that is increasingly developing and competing spurs companies to work harder in improving the quality of human resources because the quality of good human resources can increase productivity and achievement. To spur employee enthusiasm, it is necessary to carry out selection / assessment activities for the best / outstanding employees at each period. Performance appraisal must be done fairly, realistically, valid and relevant to the work done, besides that it must be free from discrimination. To determine the selection of the best employees, a decision support system and accurate and reliable calculations or methods such as the AHP (Analytical Hierarchy Process) method are needed in a company. The Decision Support System for determining the best employee using the AHP method will produce valid and useful information for administrative employee decisions such as promotions, training, transfers, including rewards and other decisions, Research will be carried out by looking at several criteria, namely work discipline, work quality, attendance, honesty, work behavior, work responsibility, then the ranking process is carried out.